Analysis of thermal loading parameters for finite-element model of thermo-impulse cleaning of metal parts’ surfaces - Жданов, О. А.; Дибський, П. О.; Лосев, О. В. (Proceedings of National Aviation University, 2003)
The main thermo-physical parameters controlling the process of thermo-impulse cleaning of metal parts’ surfaces for installation that was designed at the department of "Technology of flying vehicle manufacturing" at the National Aerospace University "KhAI" have been studied by means of finite-element parametric modeling